High-performance activated carbon from polyaniline for capacitive deionization - Zornitta, Rafael L.; García-Mateos, Francisco José; Lado, Julio J.; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Hammer, Peter; Ruotolo, Luis A.M. (Elsevier, 2017)
Activated carbons prepared using polyaniline (PAni), a N-containing precursor, doped with different anions were successfully employed in this work as electrode materials for capacitive deionization. The aim of this research was to investigate the effect of chloride (Cl ), p-toluenesulfonate (PTS ), dodecylbenze-sulfonate (DBS ) and polystirenesulfonate (PSS ) as PAni dopants on the textural and electrochemical properties of PAni activate carbon (PAC) and evaluate their performance for desalination. It was demonstrated that textural PAC properties such as microporosity could be properly tuned, resulting in a suitable proportion of micro- and mesoporosity by using different doping anions. Furthermore, it was observed that the higher the oxygen content the higher the electrode hidrophilicity due to introduction of surface polar groups, as identified by XPS. These groups were found to be the most important variable influencing on the PAC electrosorption capacity and energy efficiency. The highest specific adsorption capacity (14.9 mg g 1), along with the lowest specific energy consumption, was obtained using the PTS-doped PAC electrode. Considering its high capacity, low-cost and ease of syn thesis, PAC/PTS seems to be a promising electrode for CDI.
Keywords: Carbon; polyaniline; capacitive deionization